Djetneut tells some Raven tales - Djetneut Kul'u; Agripina Kul'u; Alexander King (Alexander King, 1998)
Djetneut tells a 3 (or more?) Raven tales to ethnographer and her daughter Pina. Born near Khailino on tundra in Yaranga. Spoke limited Russian. Birthday is approximation. Mother of one son. Learned Russian as 4th language starting in grad school and extensive residence in Kamchatka (1995 5mos, 1997-98 17 months). Had very good conversational skills by summer 1997 and fluent by early 1998, at least in listening. Has thick American accent. Knows a few words of Koryak for social situation.